Mapping faults in the laboratory with seismic scattering 2: the modelling perspective. Issue 2 (11th March 2023) - King, Thomas; De Siena, Luca; Zhang, Yi; Nakata, Nori; Benson, Philip; Vinciguerra, Sergio
SUMMARY: Peak delays of acoustic emission (AE) data from rock deformation laboratory experiments are sensitive to both sample heterogeneities and deformation-induced impedance contrasts inside the sample. However, the relative importance of stochastic heterogeneity and discontinuities is uncertain, as is the relationship between peak delays and applied stress and strain. In the companion paper, we presented and analysed peak delay data from AE recorded in a sandstone sample that was triaxially deformed to failure. Here, we simulate P–SV waveforms of dominant frequency 200 kHz in a 2-D isotropic, layered medium using realistic parameters derived from the laboratory experiments previously analysed. Our aim is to provide a physical interpretation of the laboratory findings and constrain the role of a proxy of the evolving fault zone on peak delays. We consider a 2-D fault zone embedded in a host material that simulates the fracture plane as a more compliant layer and allows us to numerically investigate variations in peak delay. Measurements of background parameters, including isotropic velocity and fault thickness were optimized using laboratory data via an evolutionary algorithm. Our simulations clarify that near-source peak delay observations are sensitive to the heterogeneity within zones of intense strain even when far-field approximations are not valid. This sensitivity manifests through the arrival of trapped waves within the layer that is coupled with multiple reflections from the sample boundaries. Substantial uncertainties remain on the possibility of inverting sample parameters with 2-D simulations and such complex physics. Our combined experimental and modelling study suggests that peak delays and coda parameters are sensitive to the heterogeneity caused by faulting and strain variations at different stages of fault-inducing slow deformation.